Atomic spectrometry update: review of advances in the analysis of clinical and biological materials, foods and beverages. Issue 3 (23rd February 2023) - Patriarca, Marina; Barlow, Nicola; Cross, Alan; Hill, Sarah; Robson, Anna; Tyson, Julian
Abstract : This review discusses developments in elemental mass spectrometry, atomic absorption, emission and fluorescence, XRF and LIBS, as applied to the analysis of specimens of clinical interest, foods and beverages. Sample preparation procedures and quality assurance are also included. Abstract : This update covers publications from the second half of 2021 to the middle of 2022. Advances in the application of atomic spectrometry techniques to clinical and biological materials, foods and beverages are reviewed in the text, highlighting their key features. Technical details of sample collection and preparation, as well as progresses with analytical techniques are considered and three tables complement the text, summarising details of a larger spectrum of publications. During this period, the trend toward the application of multi-element techniques, such as EDXRFS, ICP-MS and LIBS continued, in particular for food authenticity studies. Triple quadrupole ICP-MS is becoming increasing popular, as it is less affected by interferences, as well as LIBS and XRF, that require minimal sample preparation. However, AAS is still considered a valid alternative for single or a limited number of elements: as in previous years, numerous pre-concentration techniques were presented, some of which explored "greener" reagents. The interest in NPs continued, both as a potential exposure risk and for their application as tags of biological materials, and led to a wider application of spICP-MS. Chromium speciation in food received more attention than usual during this period, providing evidence that the carcinogenic species Cr VI was not present. A number of studies covered the application of atomic spectrometry techniques for the indirect determination of biological macromolecules, including an interesting application of LIBS for the rapid detection of the immune response to SARS-CoV-2.